Traces of Social and Intercultural Experiences of Students in International Mobility: from Friendship Ties to "Hardship" - Medeiros, Cintia Rodrigues de Oliveira (2017)
Among the changes in the global labor market is the demand for a professional profile that includes an intercultural vision, among other features. Since the early 2000s, the Brazilian government has intensified its presence in international mobility programs for higher education students. Accordingly, Brazilian universities also encourage students to have the experience of exchange, adhering to various national and international mobility programs. This research aims to gather and analyze social and cultural experiences of Business Administration students of the Federal University of Uberlândia during the period they lived in international mobility. Therefore, we conducted semi-structured interviews with eight Business Administration students that participated in International Mobility programs in the last two years. The technique of content analysis was used for analyzing the corpus. As a result, we identified that the social experiences of students in international mobility are marked by friendship ties, adventure, knowledge, negotiated speech and moments of "hardship".